The scholar who created and breath life to the phenomenological pedagogy in Italy - Vanna Iori (University of Bologna, 2016)
Piero Bertolini was one of the most important educational theorists in Italy and definitively the first referring in his works to Husserl's phenomenology. He initiated a pedagogical school of thought that regards education as an intentional act and not as a technical one, which can be presented as responsibility and a search for meaning. From this perspective, his studies focused on the relationship between educational sciences, on intentionality and Lebenswelt educational paradigms, relating them to the concrete educational experience. The foresights originated by Bertolini are more than ever updated to understand the decline of humanity in human relationships in the contemporary world.